Effectiveness of Pineapple Waste (Ananas comosus) as Natural Disinfectant in Milk Cans - Eulis Tanti Marlina; E. Harlia; Y. A. Hidayati (Fakultas Peternakan, Universitas Padjadjaran, 2018)
This study aims to study the effectiveness of pineapple fruit waste (peelsand hump) as a natural source of disinfectant in the disinfection process of milk can. The study was conducted descriptively with three treatments, namely ethanol 96% (P1), pineapple peelsextract 100% (P2), and pineapple hump extract 100% (P3). The parameters measured were bacterial inhibition zones, decrease of total bacteriaand Coliform. The results showed that ethanol 96%was very effective in reducing total and Coliform bacteria by producing a inhibition zone of 25.75 mm, while pineapple peelsand hump extracts were included in the medium category disinfectant by producing inhibition zones of 9.05 mm and 7.25 mm respectively. Decrease in the total number of bacteria in ethanol 96%treatment (P1), pineapple peelsextract (P2), and pineapple hump extract (P3) respectively 90.43%, 66.15%, and 55.00%, while decreasing the number of Coliform 85.68% (P1), 52.94% (P2) and 51.45% (P3). These results illustrate that pineapple waste is effective to be used as a natural disinfectant in milk cans.